PENGARUH GAME MOBILE LEGENDS TERHADAP ANTUSIAS REMAJA (USIA 19-24 TAHUN - Trandi trandi; Leo Slamet M.A (Sekolah Tinggi Teologi Imauel Pacet, 2021)
From the development of smartphones that are growing, bringing video games also increasingly advanced with features that are also growing, with this research if it can help to know in depth the effects that occur in playing games, with qualitative and quantitative research methods the authors get. The influence resulting from the development of mobile phones makes everyone enthusiastic to be more creative, with this development the game on mobile phones is increasingly developing, and this development has an impact on adolescents both physically and mentally. The resulting impact in playing excessive games will make teenagers addicted to playing